Developing Android Role Playing Game for Elementary Music Learning - Florentinus, Totok Sumaryanto; Utomo, Kamsidjo; Nugraha, Robertus. Gita Ardhy (KnE Social Sciences, 2019)
The lack of elementary student’s knowledge and interest about Indonesia’s traditional song can affect the existence of traditional songs. Elementary students prefer to listen to modern songs from the device that they have in their daily life. In the music learning process, the student feels bored because of the monotone learning method, even though music art learning process is an important process to promote student knowledge about Indonesia’s traditional songs. Innovation is needed because of this condition. For example, is the use of technological devices like mobile device in music artlearning.Thisstudyaimstodesignanddevelopanandroidrole-playinggame(RPG) for music learning, especially Indonesia’s traditional songs. This study also analyses the worthiness of android RPG game based on expert judgment validation’s score. Basedonexpertjudgmentvalidation’sscore,themusicartlearningmediacalled“Lagu Nusantara” is worthy of supporting the student to learn about basic of music learning and Indonesia’s traditional songs. The average score is 3.6 for media representation, 4 for the material which presented in this game, and 3.3 for the use of language. The worthinessofthismediaisabove90%(precisely90.83%).Inconclusion,thisRPGgame can use by teachers or students to promote music art learning process, especially about Indonesia’s traditional songs. Keywords: role-playing game, Android, music art, Indonesia’s traditional song